High performance simulations of electrokinetic flow and transport in microfluidic chips - Kler, Pablo Alejandro (2009)
This article discusses high performance numerical simulations of electrokinetic flow and transport phenomena in microfluidic chips. Modeling grounds on conservation equations of mass, momentum and electric charge in the framework of continuum mechanics. Two examples of interest in microfluidics are considered as study cases. Three dimension effects and whole chip geometries are taking into account. All numerical simulations presented are performed with PETSc-FEM within a Python programming environment employing parallel computing. Computation time and parallel efficiency are measured in order to study additive Schwarz method performance as domain decomposition technique in solving common ill-conditioned microfluidics problems.